Perkembangan gonad, fekunditas dan diameter telur Hemisilurus heterorhynchus, Bleeker 1854 di sungai paparan banjir, Desa Mentulik, Kampar Kiri, Riau - Elvyra, Roza; Fitri, Febrian Lailatul; Yusfiati, Yusfiati; Khairijon, Khairijon; Wardani, Imelda (Jurnal Biologi Udayana, 2023)
Floodplain river is one of the freshwatercharacteristics of Riau Province. Selais humped fish (Hemisilurus heterorhynchus) is a demersal freshwater fish. and usually lives in tropical areas with rivers that are flood-prone. H. heterorhynchus is often caught regardless of size so that fish that are immature or have immature gonads are also caught. If this condition continues, it is likely that H. heterorhynchus will experience a population decline. Therefore it is necessary to conduct research on the reproductive biology of H. heterorhynchus to find out, gonadal development, gonado somaticindex (GSI), egg diameter, fecundity, the relationship between fecundity and body length and weight, spawning season and fish spawning patterns so that it can be used as a basis for conservation and cultivation of H. heterorhynchus . This research was conducted from October to March on the Kampar Kiri river. Gonad mature male and female fish were mostly found at the beginning of the rainy season in October and November. The highest male GSI was obtained in October (0.24%) and female in November (2.80%). Fecundity of H. heterorhynchus ranged from 6444-20654 eggs. The spawning pattern of H. heterorhynchus fish is once a year (total spawner).